2011
DOI: 10.2310/jim.0b013e3181ed30bf
|View full text |Cite
|
Sign up to set email alerts
|

Promises and Pitfalls in Erythopoietin-Mediated Tissue Protection: Are Nonerythropoietic Derivatives a Way Forward?

Abstract: The essential biological role of erythropoietin (EPO) in maintaining erythrocyte mass has been well understood for many years. Although EPO is required for the maturation of red cells, it also has strong procoagulant effects on the vascular endothelium and platelets, which limit erythrocyte losses after hemorrhage. Like other members of the type 1 cytokine superfamily, EPO has multiple biological activities. For the past 10 years, multiple investigators have shown that EPO acts as a locally produced antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 115 publications
0
42
0
Order By: Relevance
“…These regions do not contain lysine and, therefore, are not modified by carbamylation of EPO, a procedure that produces a tissue-protective compound that is unable to bind to the classic EPO receptor (11). Subsequent studies have since identified that the novel tissue-protective peptide, pHBSP, can confer protection in a number of disease models (29)(30)(31)(32)(33)(34)(35)(36)(37). The interesting aspect of pHBSP is that it has many of the pleiotropic effects of EPO.…”
Section: Discussionmentioning
confidence: 99%
“…These regions do not contain lysine and, therefore, are not modified by carbamylation of EPO, a procedure that produces a tissue-protective compound that is unable to bind to the classic EPO receptor (11). Subsequent studies have since identified that the novel tissue-protective peptide, pHBSP, can confer protection in a number of disease models (29)(30)(31)(32)(33)(34)(35)(36)(37). The interesting aspect of pHBSP is that it has many of the pleiotropic effects of EPO.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 This heterodimeric complex, the activation of which requires much higher concentrations of EPO compared with the activation of the homodimeric EPO-R, 16 has been described on nonerythroid cells. When we stained human T cells for CD131 and evaluated expression levels by flow cytometry, we observed that, although CD131 was absent on resting T cells, CD131 was detectable on both CD4 + and CD8 + T-cell subsets 24 hours after anti-CD3/anti-CD28 mAb stimulation ( Figure 10, A and B).…”
Section: Activation Of Epo Heterodimericmentioning
confidence: 99%
“…Although a short-term open trial in Mali showed no increased mortality , others (John et al, 2010) have pointed out the limited opportunity to detect thrombotic side effects, the chief concern in the wider literature (Patel et al, 2011a), on using unaltered erythropoietin. Meanwhile, there appears to be a consensus (Casals-Pascual et al, 2009;John et al, 2010) to await the outcome of basic studies of the EPO variants discussed earlier (Hand and Brines, 2011;Leconte et al, 2011;Patel et al, 2011b). Some of the potentially less damaging approaches depicted in Fig.…”
Section: B Nonspecific Inhibition Of Tumor Necrosis Factormentioning
confidence: 99%
“…They fall into two main categories: carbamylated EPO (Ramirez et al, 2009;Leconte et al, 2011) and nonerythropoietic tissue-protective proteins that mimic the three-dimensional structure of EPO, such as pyroglutamate helix B-surface peptide (Patel et al, 2011b). Hand andBrines (2011) andSølling (2012) have reviewed this area. Information such as toxicity and efficacy within the wide range of activities of native EPO is still being gathered for these variants.…”
Section: B Nonspecific Inhibition Of Tumor Necrosis Factormentioning
confidence: 99%